FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR SISWA KELAS X DI SMAN 1 SUGIHWARAS BOJONEGORO - Wardani, Dian Kusuma; Hayati, Dina Nur (Universitas KH. A. Wahab Hasbullah, 2021)
Factors are things, circumstanse, or events that play a role and affect things that will happen. The level student achievement depends on the factors that influence it. There are two factors that can influence, including factors contained within students (internal factors) and factors that exist from outside students (external factors). This study aims to determine the factors that influence the learning achievement of class X students at SMAN1 Sugihwaras Bojonegoro. This research is quantitative, the research design uses multiple regression analysis. Data collection through documentation, questionnaires and report cards. The result of the research is a regression analysis model formed by predictor variables that have a significant influence on student learning outcomes, namely physical variables, interest variables, motivation variables and family environment variables. Variables that do not have a significant effect on the model are the IQ, the school environment variables and the community environment variables. The conclusio of the study is that the factors that influence the learning outcomes of class X students at SMAN 1 Sugihwaras Bojonegoro are physical, interest, motivational and family environmental.